2014
DOI: 10.1653/024.097.0127
|View full text |Cite
|
Sign up to set email alerts
|

Population Trends of the Redbay Ambrosia Beetle (Coleoptera: Curculionidae: Scolytinae): Does Utilization of Small Diameter Redbay Trees Allow Populations to Persist?

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The beetle populations are relatively cold tolerant despite their tropical origin (28) and are frequently spread through anthropogenic wood transport. The beetles persist in the landscape long after the main epidemic has killed all typical hosts (18,74). Whether they persist on suboptimal hosts or the host spectrum is broader than Lauraceae is unknown.…”
Section: Mode 1: Association With a Virulent Tree Pathogenmentioning
confidence: 99%
“…The beetle populations are relatively cold tolerant despite their tropical origin (28) and are frequently spread through anthropogenic wood transport. The beetles persist in the landscape long after the main epidemic has killed all typical hosts (18,74). Whether they persist on suboptimal hosts or the host spectrum is broader than Lauraceae is unknown.…”
Section: Mode 1: Association With a Virulent Tree Pathogenmentioning
confidence: 99%
“…Evans et al (2013) reported large declines in redbay densities across all diameter classes on the island from 2004-2009, and by 2014, the species, although persisting in the midstory at small diameters, was no longer a component in the canopy among our three sites. Recent studies indicated that the ambrosia beetle can persist in redbay stands that have trees with 2-3cm root collar diameters (Maner et al, 2014), so in future years, it will be interesting to track growth and survival of the remaining stems as they move into larger diameter classes.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of the redbay ambrosia beetle increase very rapidly in coastal forests of the southeastern US, where redbays are common and of sufficient size to serve as brood ( Figure 4; [38]). Likewise, populations decrease rapidly within a couple of years after tree death, because as trees are colonized by secondary fungi and begin to decay, they become increasingly unusable by the beetle.…”
Section: Xyleborus Glabratus and Its Fungal Associatesmentioning
confidence: 99%